Prevalence of risk factors for cardiovascular disease in Canadians 55 to 74 years of age: results from the Canadian Heart Health Surveys, 1986-1992 - Langille, DB (1999)
BACKGROUND: By 2016, the proportion of Canadians older than 65 years of age will increase to 16%, and there will be an increase in the absolute number of cases of cardiovascular disease in older Canadians. The Canadian Heart Health Surveys database provides information about this population upon which health policy related to cardiovascular disease can be based. This paper presents for the first time population-based data on the risk factors for cardiovascular disease in older Canadians. METHODS: Canadians from all 10 provinces participated in surveys of cardiovascular risk factors; health insurance registries were used as sampling frames. In each province, probability samples of 2200 adults 18 to 74 years old not living in institutions, on reserves or in military camps were asked to participate in interviews and to undergo testing at clinics for major risk factors for cardiovascular disease. RESULTS: A total of 2739 men (response rate 70%) and 2617 women (response rate 66%) aged 55 to 74 years participated in the survey and also provided follow-up clinical measurements at the clinic. Overall, 52% of participants were hypertensive, 26% had isolated systolic hypertension, and 30% had a total blood cholesterol level of 6.2 mmol/L or greater. Rates of current smoking were lower in women than men (17% v. 22%). Overall, 87% of men and 78% of women who were current smokers smoked at least 10 cigarettes per day. Only slightly more than half of participants exercised at least once a week for at least 15 minutes, and almost half had a body mass index of 27 or greater. In only 4% was no major risk factor for cardiovascular disease detected. INTERPRETATION: Significant numbers of older Canadians have one or more major risk factors for cardiovascular disease. Many of these risk factors are amenable to modification.